ЕЛЕКТРОМАГНІТНЕ ПОЛЕ ІНДУКТОРА З Ш-ПОДІБНИМ ОСЕРДЯМ ДЛЯ МАГНІТНО-ІМПУЛЬСНОЇ ОБРОБКИ МАТЕРІАЛІВ - Ращепкін , А.П.; Кондратенко, І.П.; Карлов , О.М.; Крищук , Р.С. (Інститут електродинаміки НАН України, Київ, 2019)
The method of analysis of electromagnetic processes in an inductor with a W-shaped ferromagnetic core is presented. The inductor is designed for contactless excitation in any metal plate of magnetic field pulses and high density currents. The inductor magnetic core has a movable middle part for an additional pulsed physical impact on the metal plate. Thus, the action of the inductor is for achieving a magnetoplastic effect (MPE) in metal plates with plastic deformation. Current pulses in the winding of the inductor are performed by discharging a capacitor on the circuit. A thyristor is included in the inductor circuit, which makes it possible to obtain unipolar current pulses in the inductor winding. Parallel to the capacitor, a diode is included, which makes it possible to obtain unipolar, but slowly decaying current pulses in the winding. The electrical parameters of the inductor are determined by computer simulation for a quasi-stationary mode using the finite element method for the set of current values. It takes into account the magnetization curve of the magnetic core. The transient current is determined from the solution of the nonlinear differential equation of the electrical circuit. The current allows us to solve the transient electromagnetic problem in a metal plate using the finite element method. The conditions for obtaining a unipolar pulsed electromagnetic field in a metal plate are investigated. The method in this article is used for calculation electromagnetic problems in the inductor with magnetic core 164x100x33 mm. Magnetic forces which acting on the movable part of the magnetic circuit and on the metal plate is obtained.  References 11, figures 6.